The Anne Boleyn Illusion is a six-fingered salute to sensory remapping - Newport, Roger; Wong, Dominic Y.; Howard, Ellen M.; Silver, Eden (SAGE Publications, 2016)
The Anne Boleyn Illusion exploits the somatotopic representation of touch to create the illusion of an extra digit and demonstrates the instantaneous remapping of relative touch location into body-based coordinates through visuo-tactile integration. Performed successfully on thousands, it is also a simple demonstration of the flexibility of body representations for use at public events, in schools or in the home and can be implemented anywhere by anyone with a mirror and some degree of bimanual coordination.